CHITIN- AND CHITOSAN BIOSORBENTS FROM CITRIC A CID MYCELIAL INDUSTRIAL WASTE - L. V. Novinyuk; D. K. Kulyov; I. V. Negrutsa; P. Z. Velinzon (Пищевые системы)
The goal of this study is to examine sorption capacity of chitin-glucan (ChGC) and chitosan-glucan (CsGC) biopolymer complexes extracted from the fungus Aspergillus niger mycelium. According to the findings chitosanglucan complex sorbs lead and copper ions (130–140 mg/g) better than chitin-glucan complex (50–80 ex mg/g). Langmuir theoretical model with R2= 0,996 determination coefficient well describe sorption isotherms. It is shown the chelate complex formation compound character based on ion and coordination bonds by chitin and chitosan biopolymers is more complex. According to test results the production of chitin and chitosan containing biopolymers from citric acid production mycelium by-products has a good future.  The above biopolymers have a functional use. Besides of that they sorbs heavy metals and radionuclide ions.